"Negotiorum Gestio" in Family Medicine, Informed Consent Obtainment, and Disciplinary Responsibility. (24th March 2016) - Birkeland, Søren
Abstract : Introduction. Negotiorum gestio (NG) denotes an action where a person well intendedly acts on behalf of another without obtaining the latter's prior consent. In broad terms, NG-like actions have played a considerable role in health care provision. In some settings, health care delivery with only little or presumed patients' consent has been the rule rather than the exception. However, bioethical principles regarding patient autonomy and obtainment of the patient's informed consent (IC) before intervention are now increasingly materialized in the law of many countries. Aim. To study legal consequences of NG in family medicine and IC handling options. Methods. Case law examination. Results. A disciplinary board case is described concerning a family doctor conducting unlawful NG by not coming up to legal IC requirements. Discussion and Conclusion. The practical and legal implications of IC and possible role of novel Shared Decision-Making approaches in coming up to regulation and bioethical demands are discussed. It is concluded that a doctor may run an unnecessary legal risk when conducting NG in decision-competent patients and furthermore it is suggested that novel Shared Decision-Making approaches could help in obtaining a rightful and practicable IC.